ChemInform Abstract: Thelepamide: An Unprecedented Ketide‐Amino Acid from Thelepus crispus, a Marine Annelid Worm. Issue 26 (1st July 2014) - Rodriguez, Jaime; Nieto, Rosa M.; Blanco, Maria; Valeriote, Frederick A.; Jimenez, Carlos; Crews, Phillip
Abstract The title compound (I) shows modest activity against leukemia cells (IC50 = 5 μg/mL).